Overview of Important Micronutrients Supplementation in Preterm Infants after Discharge: A Call for Consensus - Laura Ilardi; Alice Proto; Federica Ceroni; Daniela Morniroli; Stefano Martinelli; Fabio Mosca; Maria Lorella Giannì (Life, 2021)
Preterm infants have a lower level of nutrient body stores and immature body systems, resulting in a higher risk of malnutrition. Imbalanced complementary feeding could lead to further risk of nutritional deficits and excesses. However, evidence on their nutritional requirements following hospital discharge is limited. When planning complementary feeding, appropriate micronutrient intake should be considered for their critical role in supporting various body functions. This narrative review summarizes the need for iron, zinc, vitamin D, calcium, phosphate and long-chain polyunsaturated fatty acids (LCPUFAs) supplementation in preterm infants during complementary feeding. Regarding iron and vitamin D, the scientific community is reaching an agreement on supplementation in some categories of prematures. On the contrary, there is still not enough evidence to detail possible recommendations for LCPUFAs, zinc, calcium and phosphorus supplementation. However, these micronutrients are paramount for preterms’ health: LCPUFAs can promote retinal and brain development while calcium and phosphorus supplementation is essential to prevent preterms’ metabolic bone disease (MBD). Waiting for a consensus on these micronutrients, it is clear how the knowledge of the heterogeneity of the prematures population can help adjust the nutritional planning regarding the growth rate, comorbidities and comprehensive clinical history of the preterm infant.